Question
upstudy study bank question image url

)find the value of \( A^{1} \cap B^{1} \cap C^{1} \) a). Make \( m \) the subject of the formula \( y=a \sqrt{\frac{m-3}{m-9}} \) ). find the value of \( m \) if \( y=4 \) and \( a=2 \)

Ask by Todd Brewer. in Nigeria
Feb 24,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

A¹ ∩ B¹ ∩ C¹ = (A ∪ B ∪ C)¹. m = (9y² – 3a²)/(y² – a²). For y = 4 and a = 2, m = 11.

Solution

Below is one acceptable solution. ────────────────────────────── Problem 1: Find the value of A¹ ∩ B¹ ∩ C¹ In many texts the notation A¹ is used to denote the complement of the set A (often written as Aᶜ). In that case the intersection   A¹ ∩ B¹ ∩ C¹ is the set of all elements which are not in A, not in B, and not in C. By one of De Morgan’s Laws we have   A¹ ∩ B¹ ∩ C¹ = (A ∪ B ∪ C)¹. That is, it is the complement of (A ∪ B ∪ C). (Without any further information about the sets A, B, and C, this is the most that can be said.) ────────────────────────────── Problem 2(a): Make m the subject of the formula   y = a √[(m – 3)/(m – 9)]. Step 1. Square both sides to eliminate the square root:   y² = a² · (m – 3)/(m – 9). Step 2. Multiply both sides by (m – 9) (assuming m ≠ 9):   y² (m – 9) = a² (m – 3). Step 3. Expand and bring like terms together:   y² m – 9y² = a² m – 3a². Step 4. Rearrange to group m terms on one side:   y² m – a² m = 9y² – 3a². Factor m out:   m (y² – a²) = 9y² – 3a². Step 5. Solve for m:   m = (9y² – 3a²)/(y² – a²). For a slightly neater form, you may factor 3 from the numerator:   m = [3(3y² – a²)]/(y² – a²), with the condition that y² ≠ a² (so that the denominator isn’t zero). ────────────────────────────── Problem 2(b): Find the value of m if y = 4 and a = 2. Substitute y = 4 (so that y² = 16) and a = 2 (so that a² = 4) into the expression we obtained:   m = (9y² – 3a²)/(y² – a²)     = (9·16 – 3·4)/(16 – 4)     = (144 – 12)/12     = 132/12     = 11. ────────────────────────────── Final Answers: 1. A¹ ∩ B¹ ∩ C¹ = (A ∪ B ∪ C)¹ (i.e. the complement of A ∪ B ∪ C). 2. (a) m = (9y² – 3a²)/(y² – a²)           (b) For y = 4 and a = 2, m = 11.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To find \( A^{1} \cap B^{1} \cap C^{1} \), we need to break down the problem into smaller tasks. First, let's make \( m \) the subject of the formula \( y = a \sqrt{\frac{m-3}{m-9}} \). Start by isolating the square root: 1. Divide both sides by \( a \): \( \frac{y}{a} = \sqrt{\frac{m-3}{m-9}} \) 2. Square both sides: \( \left(\frac{y}{a}\right)^2 = \frac{m-3}{m-9} \) 3. Cross-multiply: \( (m-3) = \left(\frac{y^2}{a^2}\right)(m-9) \) 4. Rearranging gives us: \( ay^2m - 9y^2 = am - 3a \) 5. Factor out \( m \): \( m(ay^2 - a) = 9y^2 - 3a \) 6. Thus, \( m = \frac{9y^2 - 3a}{ay^2 - a} \). Next, we can find the value of \( m \) if \( y = 4 \) and \( a = 2 \): 1. Plugging in the values: \( m = \frac{9 \cdot 4^2 - 3 \cdot 2}{2 \cdot 4^2 - 2} \) 2. Calculate: \( m = \frac{9 \cdot 16 - 6}{2 \cdot 16 - 2} = \frac{144 - 6}{32 - 2} = \frac{138}{30} \) 3. Simplifying gives: \( m = \frac{23}{5} \). Therefore, the values obtained are \( m \) expressed in terms of \( y \) and \( a \), and the specific calculation yields \( m = \frac{23}{5} \) when given \( y = 4 \) and \( a = 2 \).

Related Questions

ISCELÁNEA cribir, por simple inspección, el resultado de: \( \begin{array}{lll}(x+2)^{2} & \text { 14. }(x+y+1)(x-y-1) & \text { 27. }\left(2 a^{3}-5 b^{4}\right)^{2} \\ (x+2)(x+3) & \text { 15. }(1-a)(a+1) & \text { 28. }\left(a^{3}+12\right)\left(a^{3}-15\right) \\ (x+1)(x-1) & \text { 16. }(m-8)(m+12) & \text { 29. }\left(m^{2}-m+n\right)\left(n+m+m^{2}\right) \\ (x-1)^{2} & \text { 17. }\left(x^{2}-1\right)\left(x^{2}+3\right) & \text { 30. }\left(x^{4}+7\right)\left(x^{4}-11\right) \\ (n+3)(n+5) & \text { 18. }\left(x^{3}+6\right)\left(x^{3}-8\right) & \text { 31. }(11-a b)^{2} \\ (m-3)(m+3) & \text { 19. }\left(5 x^{3}+6 m^{4}\right)^{2} & \text { 32. }\left(x^{2} y^{3}-8\right)\left(x^{2} y^{3}+6\right) \\ (a+b-1)(a+b+1) & \text { 20. }\left(x^{4}-2\right)\left(x^{4}+5\right) & \text { 33. }(a+b)(a-b)\left(a^{2}-b^{2}\right) \\ (1+b)^{3} & \text { 21. }(1-a+b)(b-a-1) & \text { 34. }(x+1)(x-1)\left(x^{2}-2\right) \\ \left(a^{2}+4\right)\left(a^{2}-4\right) & \text { 22. }\left(a^{x}+b^{n}\right)\left(a^{x}-b^{n}\right) & \text { 35. }(a+3)\left(a^{2}+9\right)(a-3) \\ \left(3 a b-5 x^{2}\right)^{2} & \text { 23. }\left(x^{a+1}-8\right)\left(x^{a+1}+9\right) & \text { 36. }(x+5)(x-5)\left(x^{2}+1\right) \\ (a b+3)(3-a b) & \text { 24. }\left(a^{2} b^{2}+c^{2}\right)\left(a^{2} b^{2}-c^{2}\right) & \text { 37. }(a+1)(a-1)(a+2)(a-2) \\ (1-4 a x)^{2} & \text { 25. }(2 a+x)^{3} & \text { 36. }\left(x^{2}-11\right)\left(x^{2}-2\right)\end{array} \) \( \left(a^{2}+8\right)\left(a^{2}-7\right) \)
Algebra Mexico Feb 26, 2025
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy